The Influence of Transactional Leadership, Compensation, and Perceived Organizational Support on Employee Performance in the Sales Division of PT Weva Adhijaya Textile - Amalia Putri Febrianti; Ika Korika Swasti (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2026)
Purpose - Effective human resource management is one of the crucial factors in maintaining a company's competitiveness amid the dynamic competition in the textile industry. The purpose of this study is to determine the effect of transactional leadership, compensation, and perceived of organizational support on employee performance in the sales division of PT Weva Adhijaya Textile. The phenomenon of declining sales targets over the past three years indicates a gap between management policies and employee performance results Design/methodology/approach - The research approach used was quantitative with 40 respondents from the sales division. Data was obtained from interviews and questionnaires, then the analysis technique used was Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0 software.   Originality - This study contributes to the understanding of the influence of transactional leadership, compensation, and perceived organizational support on employee performance in target-oriented fabric supplier companies Findings and Discussion - The results of this study show that transactional leadership has a insignificant effect on employee performance. However, compensation and perceived organizational support have a positive and significant effect on improve employee performance Conclusion - The analysis shows that transactional leadership does not contribute to employee performance, as the reward and punishment-based approach has proven ineffective. On the contrary, compensation plays a crucial role in improving performance. In addition, perceived organizational support also contributes to improved performance.